The Right to Run for Election in Zambia: A Preserve of the "Educated" Class? - Phiri Christopher (CAMBRIDGE UNIV PRESS, 2022)
The 2016 amendments to the Constitution of Zambia 1991 have transformed Zambia's constitutional order in many respects. Among other transformative provisions, the Constitution now requires everyone seeking elective public office to have, as a minimum qualification, a grade twelve certificate or its equivalent. This article examines the rationale for this requirement, as judicially interpreted, through the lens of the right to run for election. The article's core argument is twofold. First, that the requirement is an unwarranted restriction on the right to run for election and cannot be justified when considered in its relevant context. Secondly, that the Constitutional Court of Zambia's recent interpretation of the requirement further limits the right to run for election and in turn narrows the field of candidates from which voters may choose, potentially depriving the country of resourceful political leadership. The article concludes with a call for reform.